Strategies for Enhancing Religious Life among the Meratus Mountain Communities: Evidence from a Thematic Community Service Program - Muhammad Zainal Abidin; Arni; Mulyani; Siti Faridah (Jurnal Ilmiah Ilmu Ushuluddin, 2026)
This article examines strategies for enhancing the quality of religious life among communities in the Meratus Mountains through a Thematic Community Service Program (KKN Tematik). The study employs a qualitative field-based approach to analyze program planning, implementation strategies, and community responses to the intervention. Data were collected through observation, in-depth interviews, questionnaires, and document analysis. The findings reveal that the program develops a context-based empowerment model grounded in initial social and religious mapping of local communities. Its implementation emphasizes the integration of religious guidance with socio-economic empowerment, particularly through Qur’anic learning assistance, religious education, and small-scale entrepreneurship development. The study highlights that participatory and culturally sensitive approaches are crucial in addressing religious and social challenges in remote areas. Conceptually, these findings contribute to the broader discourse on community-based religious empowerment practices within indigenous contexts.